Electronic, Transport, and Magnetic Properties of La-Doped Ba (1-x) Fe (1.9) Pt (0 . 1) As (2) (x=0, 0.4, 0.6, 0.8) Compounds - GÜLER, ADİL; BOYRAZ, CİHAT (SPRINGER, 2018)
We briefly reported the structural variation and the nature of superconductivity properties correlating with magnetic and resistivity data of La-doped Ba1-xFe1.9Pt0.1As2 compounds. A solid-state reaction method was chosen to prepare bulk-type materials. The peak definition was studied to clarify the crystal structure of the samples, and it was observed that all samples were in ThCr2Si2-type structures, which is in harmony with similar compositions in the literature. Critical temperatures emphasizing superconductivity states have been clarified using magnetization measurements in the temperature range 5-170 K under magnetic field at 20 Oe, and the obtained results matched with resistivity measurements' results for consistency of critical temperatures. We obtained a limit doping number for the Ba1-xLa (x) Fe1.9Pt0.1As2 samples synthesized by the solid-state reaction method. Increasing La and decreasing Ba amounts in the Ba1-xLa (x) Fe1.9Pt0.1As2 samples showed a fluctuation in T (c) values with inducing superconductivity. x = 0.6 was determined to have the highest T (c) value for the Ba(0.4)La(0.6)Fe(1.9)Pt(0.1)As(2)sample, and a further increment in the amount of La revealed a deterioration in superconductivity. Replacing La with Ba should be the reason for lattice shrinkage, and slightly, the geometric factor was affected by replacing lower radius La with bigger radius Ba in the Ba0.4La0.6Fe1.9Pt0.1As2 compound.
Keywords: Lattice shrinkage; Current density; Meissner effect; La dopant effect; Superconductivity; SUPERCONDUCTIVITY